Structure-Dependent Electron Transfer Rates for Dihydrophenazine, Phenoxazine, and Phenothiazine Photoredox Catalysts Employed in Atom Transfer Radical Polymerization - Sneha, Mahima; Bhattacherjee, Aditi; Lewis-Borrell, Luke; Clark, Ian P; Orr-Ewing, Andrew J (The journal of physical chemistry. B, 2021)
Organic photocatalysts (PCs) are gaining popularity in applications of photoredox catalysis, but few studies have explored their modus operandi. We report a detailed mechanistic investigation of the electron transfer activation step of organocatalyzed atom transfer radical polymerization (O-ATRP) involving electronically excited organic PCs and a radical initiator, methyl 2-bromopropionate (MBP). This study compares nine N-aryl modified PCs possessing dihydrophenazine, phenoxazine, or phenothiazine core chromophores. Transient electronic and vibrational absorption spectroscopies over subpicosecond to nanosecond and microsecond time intervals, respectively, track spectroscopic signatures of both the reactants and products of photoinduced electron transfer in N,N-dimethylformamide, dichloromethane, and toluene solutions. The rate coefficients for electron transfer exhibit a range of values up to ∼1010 M-1 s-1 influenced systematically by the PC structures. These rate coefficients are an order of magnitude smaller for catalysts with charge transfer character in their first excited singlet (S1) or triplet (T1) states than for photocatalysts with locally excited character. The latter species show nearly diffusion-limited rate coefficients for the electron transfer to MBP. The derived kinetic parameters are used to model the contributions to electron transfer from the S1 state of each PC for different concentrations of MBP. Comparisons of singlet and triplet reactivity for one of the phenoxazine PCs reveal that the rate coefficient kET(T1) = (2.7 ± 0.3) × 107 M-1 s-1 for electron transfer from the T1 state is 2 orders of magnitude lower than that from the S1 state, kET(S1) = (2.6 ± 0.4) × 109 M-1 s-1. The trends in bimolecular electron transfer rate coefficients are accounted for using a modified Marcus theory for dissociative electron transfer.Organic photocatalysts (PCs) are gaining popularity in applications of photoredox catalysis, but few studies have explored their modus operandi. We report a detailed mechanistic investigation of the electron transfer activation step of organocatalyzed atom transfer radical polymerization (O-ATRP) involving electronically excited organic PCs and a radical initiator, methyl 2-bromopropionate (MBP). This study compares nine N-aryl modified PCs possessing dihydrophenazine, phenoxazine, or phenothiazine core chromophores. Transient electronic and vibrational absorption spectroscopies over subpicosecond to nanosecond and microsecond time intervals, respectively, track spectroscopic signatures of both the reactants and products of photoinduced electron transfer in N,N-dimethylformamide, dichloromethane, and toluene solutions. The rate coefficients for electron transfer exhibit a range of values up to ∼1010 M-1 s-1 influenced systematically by the PC structures. These rate coefficients are an order of magnitude smaller for catalysts with charge transfer character in their first excited singlet (S1) or triplet (T1) states than for photocatalysts with locally excited character. The latter species show nearly diffusion-limited rate coefficients for the electron transfer to MBP. The derived kinetic parameters are used to model the contributions to electron transfer from the S1 state of each PC for different concentrations of MBP. Comparisons of singlet and triplet reactivity for one of the phenoxazine PCs reveal that the rate coefficient kET(T1) = (2.7 ± 0.3) × 107 M-1 s-1 for electron transfer from the T1 state is 2 orders of magnitude lower than that from the S1 state, kET(S1) = (2.6 ± 0.4) × 109 M-1 s-1. The trends in bimolecular electron transfer rate coefficients are accounted for using a modified Marcus theory for dissociative electron transfer.